Development of a sports nutrition knowledge questionnaire for elite track and field athletes - Weerasinghe, Kalani; Jayawardena, Ranil; Trakman , Gina; Madhujith , Terrence; P Hills, Andrew; Sudheera Kalupahana , Nishan (World Nutrition Journal, 2024)
Background: Satisfactory nutrition knowledge among athletes is important to encourage proper dietary habits to overcome deficiencies and enhance sports performance. Identifying knowledge gaps in sports nutrition is essential for improving athletes' understanding through a tool that evaluates both general nutrition knowledge (GNK) and sports nutrition knowledge (SNK). This study aims to develop the Athletic Sports Nutrition Knowledge Questionnaire (A-SNKQ) specifically for Sri Lankan track and field athletes. Methods: The development of the A-SNKQ followed an extensive step-wise approach. Firstly, a systematic literature review was conducted on existing SNK questionnaires for athletes. Secondly, sports nutrition guidelines were incorporated into the questionnaire. Thirdly, information from local literature was gathered to ensure contextual relevance. Lastly, a qualitative study involving key athletic stakeholders was conducted to gain cultural insights. Results: The final version of the questionnaire consists of 32 questions in 12 sub-sections under two main sections: GNK section covers macronutrients, micronutrients, energy balance, hydration, and weight management, SNK section addresses carbohydrate loading, pre-training, training and post-training meals, sports supplements, supplement label reading, isotonic drinks, doping, and relative energy deficiency syndrome in sports. Conclusions: The GNK section addresses the fundamental nutritional concepts, while SNK focuses on the knowledge associated with the sporting performance of athletes.